On the Rosenthal inequality for mixing fields - Fazekas, L.; Kukush, A.G.; Tómács, T. (Український математичний журнал, 2000)
A proof of the Rosenthal inequality for α-mixing random fields is given. The statements and proofs are modifications of the corresponding results obtained by Doukhan and Utev.